THEORIES OF EVALUATING THE ECONOMIC EFFECTIVENESS OF DIGITAL TRANSFORMATION IN THE BUILDING SYSTEM OF THE REGION (Marketing Journal, 2025)
The article analyzes theoretical approaches to assessing the economic efficiency of digital transformation in the regional construction system. The impact of digital technologies on efficiency, cost -optimization factors, and the conceptual theoretical mode l for evaluation are substantiated.
Keywords: digital transformation; construction system; economic efficiency; digitalization; BIM technologies; digital model; performance indicators; innovative infrastructure; resource efficiency; evaluation methodology